Liver copper concentrations in cull cattle in the UK: are cattle being copper loaded? - Kendall, Nigel R.; Holmes-Pavord, H.R.; Bone, P.A.; Ander, E. Louise; Young, Scott D. (BMJ Publishing Group, 2015)
With the release of the Department for the Environment, Food and Rural Affairs/Advisory Committee on Animal Feed Guidance Note for Supplementing Copper to Bovines it was noted that the current copper status of the national herd was not known. Liver samples were recovered from 510 cull cattle at a single abattoir across a period of three days. The samples were wet-ashed and liver copper concentrations determined by inductively coupled plasma mass spectrometry analysis. Breed, age and previous location information were obtained from the British Cattle Movement Service. Dairy breeds had higher liver copper concentrations than beef breeds. Holstein-Friesian and ‘other’ dairy breeds had 38.3 per cent and 40 per cent of cattle above the Animal Health and Veterinary Laboratories Agency (AHVLA) reference range (8000 µmol/kg dry matter), respectively, whereas only 16.9 per cent of animals in the combined beef breeds exceeded this value. It was found that underlying topsoil copper concentration was not related to liver copper content and that age of the animal also had little effect on liver concentration. In conclusion, over 50 per cent of the liver samples tested had greater-than-normal concentrations of copper with almost 40 per cent of the female dairy cattle having liver copper concentrations above the AHVLA reference range, indicating that a significant proportion of the UK herd is at risk of chronic copper toxicity.